Three-Dimensional Carbon-Supported MoS2 With Sulfur Defects as Oxygen Electrodes for Li-O2 Batteries - Liu, Yun; Zang, Yipeng; Liu, Xinmiao; Cai, Jinyan; Lu, Zheng; Niu, Shuwen; Pei, Zhibin; Zhai, Teng; Wang, Gongming (Frontiers in Energy Research, 2020)
Recently, Li-O2 batteries considered to be the promising next-generation energy storage devices owing to their high theoretical specific energy. However due to the sluggish reaction kinetics of oxygen conversion, the practical application can’t achieve the desired results. By introducing vacancies on the MoS2 basal plane and in-situ synthesized method, we demonstrated the excellent catalysis of MoS2-x for oxygen redox kinetics to improve the Li-O2 batteries performance. The prepared MoS2-x displays the small polarization with potential gap of 0.59 V and high discharge capacity of 8851 mA h g-1 at a current density of 500 mA g-1. The improved performances are mainly attributed to abundant S defects and plentiful diffusion channels in the MoS2-x/carbon 3D structural cathodes to adsorb gaseous oxygen, reaction intermediates and discharge products. To the best of knowledge, the fabricated structures have been regarded as one of the excellent oxygen conversion catalysts from 3D network design and surface modulation, offering an open vision for the designing Li-O2 catalysts and beyond.